24.8k views
5 votes
Solve the equation. Enter the answer in radical form, and then use a calculator to approximate the solution to two decimal places, if necessary.

(x + 5.6)2 = 1.75

User OhmzTech
by
5.7k points

2 Answers

1 vote

Answer:

x = sqrt(1.75) - 5.6, -sqrt(1.75) - 5.6,

x ≈ -4.28, -6.92

Explanation:

(x + 5.6)² = 1.75

(x + 5.6) = +/- sqrt(1.75)

x = +/- sqrt(1.75) - 5.6

x ≈ -4.28, -6.92

User DamienG
by
5.6k points
2 votes

Answer:

x = -5.6 ±sqrt(1.75)

x≈-4.28 x≈-6.92

Explanation:

(x + 5.6)^2 = 1.75

Take the square root of each side

sqrt((x + 5.6)^2) = ±sqrt(1.75)

x+5.6 = ±sqrt(1.75)

Subtract 5.6 from each side

x+5.6 -5.6 = -5.6 ±sqrt(1.75)

x = -5.6 ±sqrt(1.75)

x= -5.6 + sqrt(1.75) x = -5.6 - sqrt(1.75)

x≈-4.27712 x≈-6.92288

x≈-4.28 x≈-6.92

User Liteye
by
5.2k points